TEKNOLOGI SISTEM BOSTER PADA BUDIDAYA LELE: DALAM PERSPEKTIF KOMUNIKASI DI DESA JAMBEWANGI KECAMATAN SEMPU KABUPATEN BANYUWANGI - Widjayanthi, Lenny; Mauladani, Zulfia Adi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
This purposes of the research were explaining the process of communication that occurred in the process of the adoption of a Booster system innovation in catfish farming. Determination of research area is done purposively in Jambewangi Village, Sempu Subdistrict, Banyuwamgi District. The subject of the research is chosen purposively. Data collection was carried out for 5 months from October 2018-March 2019 using indepth interviews, observations and documents. The research informants consisted of 3 people who adopted the booster system and 1 person who decided not to adopt. Data analysis used Miles and Huberman. The results of the research showed that the innovation adoption process was carried out through some stages, namely knowledge, persuasion, decision, implementation and confirmation. The community has different knowledge about the booster system, the booster system has been known since 2014, to improve knowledge and skills in the booster system, catfish farmers attend trainings held in various cities. It took between 3-6 months to decide to adopt, the informant refused to adopt the booster system after knowing that the pond model used was different from the pond in the previous system culture. The informants did not implement a complete booster system because the multivitamins were given as needed. Catfish farmers decided to continue cultivating catfish with a booster system for the following year. Each stage that is passed uses interpersonalcommunication channels to exchange messages. The speed at which an innovation was adopted was influenced by the nature of the innovation, namely relative advantage, compatibility, complexity, triability and observability.